Exploring the foundations of the intercultural policy paradigm: a comprehensive approach. Issue 2 (3rd March 2016) - Zapata-Barrero, Ricard
Abstract : In this second decade of the twenty-first century, interculturalism is emerging as a new policy paradigm to deal with diversity dynamics. It is basically viewed as a set of policies sharing one basic idea: that the interaction among people from different backgrounds matters. Its concerns are to intervene politically and to propose a way to manage the dynamics of diversity, based on exchange and interpersonal relations. I propose exploring a foundational internal debate, based on the premise there are at least three different, but complementary, normative strands: contractual, cohesion and constructivist strands. My ultimate purpose is to defend a comprehensive view, grounded on the argument that no one can have the sole authority to define intercultural policy, since the three strands can be applied at different moments, according to different purposes. The challenge is for policy managers to be able to achieve a balance between the three policy drivers.